2019
DOI: 10.1088/1361-6528/ab1bea
|View full text |Cite
|
Sign up to set email alerts
|

Raman characterization of single-crystalline Ga0.96Mn0.04As:Zn nanowires realized by ion-implantation

Abstract: Recent progress in the realization of magnetic GaAs nanowires (NWs) doped with Mn has attracted a lot of attention due to their potential application in spintronics. In this work, we present a detailed Raman investigation of the structural properties of Zn doped GaAs (GaAs:Zn) and Mn-implanted GaAs:Zn (Ga 0.96 Mn 0.04 As:Zn) NWs. A significant broadening and redshift of the optical TO and LO phonon modes are observed for these NWs compared to as-grown undoped wires, which is attributed to strain induced by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Interestingly, the hole concentration reduced to a value of (2.5±0.5) ×10 19 cm −3 after annealing the NWs. Recently, we showed that annealing of GaAs:Zn NWs results in the formation of a crystalline As/oxide shell around the NWs [35]. The line shape analysis indicates that holes are trapped or compensated by defects present in the c-As/ oxide shell or by interface imperfections.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, the hole concentration reduced to a value of (2.5±0.5) ×10 19 cm −3 after annealing the NWs. Recently, we showed that annealing of GaAs:Zn NWs results in the formation of a crystalline As/oxide shell around the NWs [35]. The line shape analysis indicates that holes are trapped or compensated by defects present in the c-As/ oxide shell or by interface imperfections.…”
Section: Resultsmentioning
confidence: 98%
“…In current research, quasi-one-dimensional (1D) semiconductor nanostructures have attracted tremendous attention because of their significance in understanding low-dimensional phenomena and potential applications in advanced biological, electronic and photonic nanoscale devices [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the strength of S e and S n , the SHI irradiation can be utilized to modify the Schottky barrier and transport properties in a controlled fashion either by generating the defects near the MS interface or removing the present defects by dynamic annealing [10,14]. Besides creating the defects in a controlled way, the energetic heavy ions are also used for doping and modifying the transport properties in bulk as well as nanostructures [15][16][17][18][19]. So, understanding the influence of SHI irradiation on the performance of Schottky barrier devices is an important field of research with technological applications to design better radiation-hard electronic devices.…”
Section: Introductionmentioning
confidence: 99%